Chemical synthesis and immunological evaluation of new generation multivalent anticancer vaccines based on a Tn antigen analogue. Issue 17 (23rd April 2020) - Pifferi, Carlo; Ruiz-de-Angulo, Ane; Goyard, David; Tiertant, Claire; Sacristán, Nagore; Barriales, Diego; Berthet, Nathalie; Anguita, Juan; Renaudet, Olivier; Fernández-Tejada, Alberto
Abstract : A fully-synthetic anticancer vaccine candidate incorporating an hexadecavalent Tn antigen analogue display via oxime linkages induced tumor-specific IgG antibodies and cellular immune responses in mice coadministered with QS-21 as an adjuvant. Abstract : Tumor associated carbohydrate antigens (TACAs), such as the Tn antigen, have emerged as key targets for the development of synthetic anticancer vaccines. However, the induction of potent and functional immune responses has been challenging and, in most cases, unsuccessful. Herein, we report the design, synthesis and immunological evaluation in mice of Tn-based vaccine candidates with multivalent presentation of the Tn antigen (up to 16 copies), both in its native serine-linked display (Tn-Ser) and as an oxime-linked Tn analogue (Tn-oxime). The high valent vaccine prototypes were synthesized through a late-stage convergent assembly (Tn-Ser construct) and a versatile divergent strategy (Tn-oxime analogue), using chemoselective click-type chemistry. The hexadecavalent Tn-oxime construct induced robust, Tn-specific humoral and CD4 + /CD8 + cellular responses, with antibodies able to bind the Tn antigen on the MCF7 cancer cell surface. The superior synthetic accessibility and immunological properties of this fully-synthetic vaccine prototype makes it a compelling candidate for further advancement towards safe and effective synthetic anticancer vaccines.